MANAJEMEN BERBASIS SEKOLAH (MBS) - Nanda Hashifah (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2019)
One of the educational problems that our nation is currently facing iseducation quality issues. Various attempts have been made to improve the quality of national education, among others through various training and improvement teacher competence, procurement of textbooks and learning tools, improvement of educational facilities and infrastructure, and improving the quality of school management. School-Based Management provides flexibility for schools to manage their potential by involving all elements of stakeholders to achieve school quality improvement. This study uses a qualitative approach in the form of descriptive. The use of descriptive methods in this study with the aim of describing an activity of implementing the principal's leadership in implementing school-based management which first analyzes the implementation process. Implementation of School-Based Management (SBM) at SMA Al-Masthuriyah Sukabumi is participatory. The result that occurred at Al-Masthuriyah High School was that there was still a lack of initiative from school residents due to a lack of sense of belonging to the school. In solving educational problems in schools, the people who know best about these problems are the school's own residents, especially teachers, staff, principals and parents of students. The application of participatory management improves the quality and service of education so that SMA Al-Masthuriyah can compete and produce quality graduates both academically and non-academicly. SBM will be successful if the school community has the initiative in carrying out their work and the initiative of each individual is appreciated.